Pemecahan Masalah Usaha Dan Energi Dengan Model Pembelajaran Berbasis Proyek Ditinjau Dari Keterampilan Berpikir Kritis Peserta Didik - Nurwahyuningsih Nurwahyuningsih; Ahmad Harjono; Satutik Rahayu (Department of Physics Education, Universitas Mataram, 2019)
The research have three aimed that include : (1) examine the effect of guided project based learning toward problem solving, (2) examine the effect of guided critical thinking ability toward problem solving, and (3) examine the interaction betweenÃÂ project based leraning and critical thinking ability toward problem solving. This research is quasi experiment with factorial 2Ãâ2 design. The population is all of class XI MIPA in SMAN 1 Narmada. The sampling tehnique is cluster random sampling which XI MIPA 3 as experiment group with project based learning model and XI MPA 2 as control group with convensional model. Tehnique of collecting data of problem solving using essay test 7 question and collecting data of critical thinking ability using essay test 5 question. Data of research is normal and homogen that showed by ÃÂ , Ãâ¡2quantificationÃ¢â°Â¤ Ãâ¡2tabelÃÂ = 9,17<11,07 and 5,17<11,07. Data of reserach is analysed by anava two way with SPSS 18.0.ÃÂ The result of anava two way test showedÃÂ that : (1) ÃÂ is 0,001 ÃÂ which H0A rejected and H1A accepted, that showed there is the effect of project based learning toward problem solving.ÃÂ (2) ÃÂ is 0,001<0,05 which H0B rejected and H1B accepted, that showed there is the effect of critical thinking ability toward problem solving. (3) ÃÂ is 0,69 > ÃÂ which ÃÂ H0AB accepted dan H1AB rejected, that showed there is not interaction between project basedÃÂ learning and critical thinking ability toward problem solving.